Analysis of Clinical Features of Kounis Syndrome Induced by Cephalosporin - Fang, Weijin; Song, Liying; Deng, Zhenzhen; Sun, Wei; Li, Zuojun; Wang, Chunjiang (Frontiers in Cardiovascular Medicine, 2022)
Background Cephalosporins are an increasingly encountered cause of Kounis syndrome. The present study examined the clinical features of cephalosporin-induced Kounis syndrome and provided references for diagnosis, prevention, treatment, and prognosis. Methods We collected cephalosporin-induced Kounis syndrome case reports by searching Chinese and English databases from the establishment of the database to October 31, 2021. Results Twenty-five patients (17 males and eight females) were included, with a median age of 61 years (range 33–92). Cephalosporins were administered via oral, intravenous and intramuscular routes. All reactions occurred within 30 min, except in two patients. Fourteen patients experienced chest pain, 19 experienced hypotension, 16 had cutaneous reactions, 10 had respiratory symptoms, and seven had gastrointestinal symptoms. Thirteen patients had elevated troponin levels, and eight patients had elevated serum tryptase levels. The electrocardiogram showed ST-segment elevation in 13 patients, depression in four patients, and elevation and depression in six patients. Coronary angiography showed normal results in 12 patients and abnormal results in 13 patients. The skin prick test was positive for cephalosporin in three patients. Twenty-four of the 25 patients recovered after being given anti-allergic and acute coronary syndrome treatment, and there was one death. Conclusions Kounis syndrome is a serious adverse reaction to cephalosporin. Clinicians should consider Kounis syndrome in every patient receiving cephalosporin and presenting with acute chest pain or anaphylactic symptoms.